Preparation of Liquid Soap Utilising Used Cooking Oil with Aloe Vera as an Antibacterial Agent - Sukro Muhab; Zahra, Shyla Noureen; Revita Nurul Rafah; Vinka Juniaty Lestari; Nurhalizah; Fabian Glorious Kenaya; Abdul Asywalul Fazri; Tri Handayani Kurniati (Chemistry and Materials, 2024)
Waste cooking oil has been repurposed in the preparation of liquid hand soap, enriched with Aloe vera extract as an antibacterial agent. To ensure the safety and efficacy of the product in bacterial inhibition, comprehensive testing of physical quality and antibacterial activity has been undertaken on the produced liquid soap. The test results affirm that the soap product complies with the Indonesian National Standard for free alkali content, acidity level (pH), foam height, foam stability, and water content. Notably, the soap exhibits a free alkali content of 0.01873%, a pH of 10, a foam height of 65 mm, and a foam stability value of 84.61%. The water content in the soap is measured at 40%. These results collectively position the soap within the criteria for high-quality soap. In the antibacterial effectiveness test against Staphylococcus aureus and Escherichia coli bacteria, the addition of Aloe vera has markedly expanded the inhibitory zone, demonstrating a significant enhancement in antibacterial activity. In light of the above, this study aims to address environmental pollution and health risks associated with improper disposal of waste cooking oil. Moreover, the addition of antibacterial Aloe vera presents an economically valuable solution by repurposing waste cooking oil into a useful product.